Comparative Study between the Effect of Melatonin and Hyaluronic acid on Induced Bone Defect Healing in Rabbit (Medico Legal Update, 2020)
This study was aimed to highlight the individual effects of melatonin (MEL) and hyaluronic acid (HA)on bone healing and repair mechanism and to investigate a possible effect, for a topical application. NewZealand rabbits used in this study were divided into three groups for two healing intervals the experimentalgroups were: 1. Experimental groups (20 rabbits): all animals subjected to surgical operation in right tibia,creating bone defect 3mm in depth and 4mm in diameter filled with 0.1ml. Hyaluronic acid gel and lefttibia bone defect filled with melatonin gel. 2. Control group (10 rabbits): induced bone defect on the rightside only. Animals’ scarifications were done in 2 weeks and 4 weeks’ durations. Routine processing andsectioning technique was performed for histological evaluation. At the 2weeks healing interval, highestmean value of all measured parameters were recorded at melatonin group while at 4 weeks, there is highsignificant difference in all parameters; (p-value 0.000) among all control and experimental groups. Asignificant number of positive effects of MEL, as well as HA, as individual compounds on the bone healingregeneration.